A recent tear in subducting plate explains seismicity and upper mantle structure of southern Costa Rica - Bourke, James (2020)
Past studies of southern Costa Rica have generated a multitude of tectonic scenarios to account for different data sets. Flat slabs, detached slabs, and slab windows have been proposed to address the uplift of the Cordillera de Talamanca (CT), cessation of volcanism, and absence of deep seismicity beneath southern Costa Rica. In this study, we investigate the crust and the upper mantle along the southwest flank of the CT using the receiver function methodology. We observe two regional positive P‐to‐S converted pulses at delay times of ∼2–4 s and ∼5–8 s. The first likely represents a gradational crust‐mantle boundary of the upper plate. The second represents a similar impedance increase ∼50–60 km deep that extends from central Costa Rica to Panama. Compared to well‐located seismicity, this boundary is offset to the NE from the Cocos plate Benioff zone beneath northern CT, and remains observable through a gap in seismicity farther to the southeast. This offset makes it difficult to interpret this feature as related to the presently subducting lithosphere. Instead, we propose that the 50–60 km deep boundary marks the Moho of a lithospheric fragment left behind under the CT in the course of Panama Triple Junction migration through Costa Rica over the last 10 Ma. Our interpretation accounts for the geophysical, geochemical, structural, and geomorphic observations in the literature explaining the complex geodynamic scenario observed in southern Costa Rica.